Strategi Penilaian Prospek Saham Telekomunikasi dengan Indikator RSI dan Stochastic - Taufiq Andre Setiyono; Mokhammad Khukaim Barkhowa; Rinwantin Rinwantin (Universitas Winaya Mukti, 2022)
Along with the increasing demand for access to data and information, the shares of telecommunication issuers are projected to become one of the resilience sectors. This study analyzes the sell signals and buy signals of the telecommunications shares listed on the IDX for the period 2019 to September 2021. The population is 18 issuers and the sample is 12 issuers selected using purposive sampling technique. This study uses a descriptive quantitative approach, in the form of analyzing, describing and summarizing phenomena from the data obtained through historical data observations. The aim is to describe in full and in depth the phenomenon under study. The results showed that 4 issuers gave a buy signal and 5 issuers showed that they had not yet shown a definite signal (recommended to hold), while 3 issuers seemed overbought and showed a sell signal. These results indicate that telecommunication stocks tend to be in demand and have good prospects. However, the RSI indicator is most reliable when adjusted for the long-term trend of stock price movements. This makes investors need to be careful to review further whether the signal shown is just a false signal or is a buy-sell signal.